Genetic diversity of Gallus sp. in Southeast Asia based on d-lopp: In silico study - Muttaqin, Zultinur; Sartika, Tike; Saputra, Ferdy (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study was conducted to analyze the matrilineal structure of Gallus sp. in Southeast Asia, especially in the D-loop region. Materials and Method: A total of 563 sequences from eight countries (Laos, Myanmar, Vietnam, Malaysia, Indonesia, Cambodia, the Philippines, and Thailand) in Southeast Asia are used in this study. Data collected from National Center for Biotechnology Information (NCBI) regarding the genus Gallus sp. in a Southeast Asian country. Data analysis was performed using MEGA 7.2 and DnaSP v6. Results: In the haplotype found in Gallus sp. in Southeast Asia, there are 89 haplotypes. Using a neighbor-joining (Nj) analysis, 89 haplotypes found three haplogroups for Gallus sp. in Southeast Asia. In Southeast Asia, the genetic diversity of the d-loop is exceptionally high, with a haplotype diversity value of 0.524 to 1. Conclusion: D-loop cannot be used as a specific marker for breeds or country-specifics. J. Adv. Vet. Anim. Res., 10(4): 817–819, December 2023 http://doi.org/10.5455/javar.2023.j738